Managerial strategies and practice in the Asian business sector - Zeyar Myo Aung, U, 1973-; Ordonez de Pablos, Patricia, 1975- (Hershey, PA : Business Science Reference, 2016)
'This book is a comprehensive reference source for theories and practices related to business integration in Asian countries'--
Includes bibliographical references and index.
Keywords: Management -- Asia